Hot Student Stories
top-5-grammar-and-spelling-checkers-to-rock-in-2019

What are the solutions of the equation (x – 3)2 + 2(x – 3) – 8 = 0? Use u substitution to solve. x = –5 and x = 1 x = –1 and x = 5 x = –1 and x = –7 x = 1 and x = 7

Mindee Nelson

in Mathematics

follow
followin
1 answer
5 views

1 answer


Kaitlin Dean on March 26, 2018

ANSWEREXPLANATIONThe given equation is that If we let then the equation becomes,We have divided the medium-term to obtain,now the factor to obtain;We factor to obtain;This means that;Gold But we know that This means that.OrTherefore


Add you answer